2016
DOI: 10.1021/acs.biochem.6b00331
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Aryl Binding Pocket Residues Results in an Unexpected Activity Switch in an Oryza sativa Tyrosine Aminomutase

Abstract: A 3,5-dihydro-5-methylidine-4H-imidazol-4-one (MIO)-dependent tyrosine aminomutase (TAM) isolated from the rice plant Oryza sativa (OsTAM) makes β-tyrosine (75%) and p-coumarate (25%) from α-tyrosine. OsTAM is the first TAM to have, although slight, native phenylalanine aminomutase (PAM) activity (3% relative to TAM activity). The active sites of OsTAM and a TcPAM from Taxus plants differ by only two residues (Y125 and N446 of OsTAM vs C107 and K427 of TcPAM) positioned similarly near the aryl ring of their su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The enzyme also showed acceptance of phenylalanine, albeit with an activity just 3% of that for tyrosine, which possibly points to the evolutionary origin of this enzyme from an ancestral plant PAL. Building on this, variations identified at two positions in the active site of OsTAM1, and the related phenylalanine-specific TcPAM, allowed mutagenic studies of the enzyme to increase binding affinity for phenylalanine . Interestingly, the variation of either (but not both) of these residues served not only to increase phenylalanine acceptance, but also to enhance overall turnover and ammonia-lyase activity .…”
Section: Structure and Mechanism Of Aromatic Amino Acid Ammonia-lyase...mentioning
confidence: 91%
See 2 more Smart Citations
“…The enzyme also showed acceptance of phenylalanine, albeit with an activity just 3% of that for tyrosine, which possibly points to the evolutionary origin of this enzyme from an ancestral plant PAL. Building on this, variations identified at two positions in the active site of OsTAM1, and the related phenylalanine-specific TcPAM, allowed mutagenic studies of the enzyme to increase binding affinity for phenylalanine . Interestingly, the variation of either (but not both) of these residues served not only to increase phenylalanine acceptance, but also to enhance overall turnover and ammonia-lyase activity .…”
Section: Structure and Mechanism Of Aromatic Amino Acid Ammonia-lyase...mentioning
confidence: 91%
“…167 Interestingly, the variation of either (but not both) of these residues served not only to increase phenylalanine acceptance, but also to enhance overall turnover and ammonia-lyase activity. 167 This alteration between TAM-and PAL-like activity is reminiscent of studies with PcPAL-Glu484Asn, where decrease in catalytic efficiency with L-phenylalanine and increase with L-tyrosine was observed. 168 These results taken together highlight the importance of fine-tuning mutations for substrate specificity which occur at positions other than the selectivity residues.…”
Section: Arylalanine Aminomutases (Pams and Tams)mentioning
confidence: 98%
See 1 more Smart Citation
“…Encouraged by the intrinsic intermolecular transaminase activities exhibited by MIO-PAMs, , we used Tc PAM and (2 S )-styryl-α-alanine to convert trans -3-arylglycidate racemates to arylserines and arylisoserines. In our previous substrate specificity study, we showed that Tc PAM has broad substrate specificity and stereoselectivity toward forming (2 R )- anti -arylserines over their (2 S )- anti -isomers, ranging from 66:34 for 4′-F-phenylserine to 88:12 for 3′–NO 2 –phenylserine .…”
Section: Introductionmentioning
confidence: 99%
“…31 The burst-phase study revealed that the aminated TcPAM (NH 2 −MIO) lifetime was long enough to transfer the amino group intermolecularly from (2S)-styrylα-alanine to various arylacrylates making enantiopure αand βarylamino acids. 21 Encouraged by the intrinsic intermolecular transaminase activities exhibited by MIO-PAMs, 29,32 we used TcPAM and (2S)-styryl-α-alanine to convert trans-3-arylglycidate racemates to arylserines and arylisoserines. In our previous substrate specificity study, we showed that TcPAM has broad substrate specificity and stereoselectivity toward forming (2R)-antiarylserines over their (2S)-anti-isomers, ranging from 66:34 for 4′-F-phenylserine to 88:12 for 3′−NO 2 −phenylserine.…”
Section: ■ Introductionmentioning
confidence: 99%